Implementation of Student Worksheets Based on Problem Based Learning to Improve Students' Critical Thinking Skills - Jayanti Syahfitri; Endang Sulaiman (Quagga: Jurnal Pendidikan dan Biologi, 2023)
In general, schools still use publisher printed worksheets which contain questions that are monotonous, not yet a place for students to hone and empower critical thinking skills. This study aims to determine the effect of applying Problem Based Learning (PBL) Student Worksheets (LKS) to improve students' critical thinking skills. This type of research is a quasi-experimental non-equivalent control group design involving 2 class X IPA as research samples. Data collection was carried out by providing test instruments for critical thinking skills before (pre-test) and after (post-test) learning. The data obtained were analyzed using prerequisite tests and hypothesis testing. The prerequisite test is the normality test through the Kolmogorov-Smirnov test and the homogeneity test through the Levene test. Furthermore, the data were analyzed by independent t-test. The results showed that the average score for critical thinking skills for the experimental class (XI) was 80, while for the control class (X2) the average score for critical thinking skills was 68.64. Thus it can be concluded that the application of Problem Based Learning (PBL) based worksheets has an influence on improving students' critical thinking skills compared to classes that apply publisher printed worksheets. These findings confirm that learning, especially biology learning, requires learning innovations such as teaching materials, so as to facilitate students to be actively involved, collaborative, and critical of problem solving.